Soft X-ray tomography reveals variations in B. subtilis biofilm structure upon tasA deletion - Chatzimpinou, Anthoula; Diehl, Anne; Harhoff, A. Tobias; Driller, Kristina; Vanslembrouck, Bieke; Chen, Jian-Hua; Kairišs, Kristaps; Loconte, Valentina; Le Gros, Mark A.; Larabell, Carolyn; Turgay, Kürsad; Oschkinat, Hartmut; et al. (npj Biofilms and Microbiomes, 2025)
Bacterial biofilms are complex cell communities within a self-produced extracellular matrix, crucial in various fields but challenging to analyze in 3D. We developed a “biofilm-in-capillary” growth method compatible with full-rotation soft X-ray tomography, enabling high-resolution 3D imaging of bacterial cells and their matrix during biofilm formation. This approach offers 50 nm isotropic spatial resolution, rapid imaging, and quantitative native analysis of biofilm structure. Using Bacillus subtilis biofilms, we detected coherent alignment and chaining of wild-type cells towards the oxygen-rich capillary tip. In contrast, the ΔtasA genetic knock-out showed a loss of cellular orientation and changes in the extracellular matrix. Adding TasA protein to the ΔtasA strain restored matrix density and led to cell assembly compaction, but without the chaining observed in wild-type biofilms. This scalable and transferable approach opens new avenues for examining biofilm structure and function across various species, including mixed biofilms, and response to genetic and environmental factors.
Gesehen am 05.02.2025